PENGARUH AUDIT FEE, SOLVABILITAS, LIKUIDITAS, PROFITABILITAS, UKURAN PERUSAHAAN DAN UMUR PERUSAHAAN TERHADAP AUDIT REPORT LAG PADA MASA PANDEMI COVID-19 - Fatimah Hidayati; Noer Sasongko (ITB AAS INDONESIA, 2024)
Audit report lag refers to the duration, measured in days, it takes for an auditor to finish their audit tasks, starting from the closing date of the financial year and ending on the date when the audited financial statements are issued. The objective of this study is to examine the impact of audit fees, solvency, liquidity, profitability, company size, and company age on the delay in audit reports during the Covid-19 epidemic for companies listed in the IDX80 Index from 2020 to 2022. The sample approach employed in this investigation was purposive sampling. There are 114 companies that meet the criteria to be considered as observation units. The employed analytical technique is multiple linear regression analysis. The findings offer factual proof that the solvency, liquidity, profitability, and size of a corporation have an impact on the delay in issuing audit reports. However, the audit costs and the age of the company have no impact on the delay in the issuance of the audit report.